Characterization of the N-terminal Tail Domain of Histone H3 in Condensed Nucleosome Arrays by Hydrogen Exchange and NMR - Kato, Hidenori (2009)
The N-terminal tail domains (NTDs) of histones play important roles in the formation of higher-order structures of chromatin and the regulation of gene functions. Although the structure of the nucleosome core particle has been determined by X-ray crystallography at near-atomic resolution, the histone tails are not observed in this structure. Here, we demonstrate that large quantities of nucleosome arrays with well-defined DNA positioning can be reconstituted using specific DNA sequences and recombinant isotope-labeled histones, allowing for the investigation of NTD conformations by amide hydrogen exchange and multi-dimensional nuclear magnetic resonance (NMR) methods. We examined the NTD of Drosophila melanogaster histones H3 in condensed nucleosome arrays. The results reveal that the majority of the amide protons in the NTD of H3 are protected from exchange, consistent with the NTDs having formed folded structures. Our study demonstrates hydrogen exchange coupled with NMR can provide residue-by-residue characterization of NTDs of histones in condensed nucleosome arrays, a technique that may be used to study NTDs of other histones and those with post-translational modifications.